2017
DOI: 10.3329/nimcj.v8i1.32396
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous blastomycosis : A Rare Case

Abstract: Cutaneous blastomycosis lesion is most often originate from a Primary pulmonary infection which disseminates through the blood or lymphatics to involve the skin. During the manifestations of cutaneous lesion in case of secondary blastomycosis, the primary pulmonary infection is frequently subclinical. Here we report a case that illustrates the difficulty in diagnosing a case of cutaneous blastomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Randhawa et al in their review [11] mentioned two authentic cases of blastomycosis from India including one each from Uttar Pradesh [12] and Madhya Pradesh [13]. Our review has located seven more indigenous cases in India -one authentic each from Haryana [14], Uttar Pradesh [15], Himachal Pradesh [16], two misdiagnosed cases from Gujarat [17,18], and one authentic case each form Arunachal Pradesh [19], Andhra Pradesh [20], Tamil Nadu [21] and Kerala [22] and one each from Bangladesh [23] and Nepal [24]. Brief clinical and demographic feature of these cases and our own case from h are described in the table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Randhawa et al in their review [11] mentioned two authentic cases of blastomycosis from India including one each from Uttar Pradesh [12] and Madhya Pradesh [13]. Our review has located seven more indigenous cases in India -one authentic each from Haryana [14], Uttar Pradesh [15], Himachal Pradesh [16], two misdiagnosed cases from Gujarat [17,18], and one authentic case each form Arunachal Pradesh [19], Andhra Pradesh [20], Tamil Nadu [21] and Kerala [22] and one each from Bangladesh [23] and Nepal [24]. Brief clinical and demographic feature of these cases and our own case from h are described in the table 1.…”
Section: Discussionmentioning
confidence: 99%
“…In the same year Panja [10] also described a case of generalized blastomycosis with nodular skin lesions and yeast-like cells in skin scrapings; obviously it was again a case of misdiagnosis. Randhawa et al [11] have reviewed the 11 cases of blastomycosis reported in India including seven misdiagnosed, four authentic cases comprising two imported ones and two autochthonous cases including one from Uttar Pradesh and the other from Madhya Pradesh Subsequent to this review, there have been six reports of blastomycosis including two misdiagnosed cases from Gujarat [14,15] and authentically diagnosed comprising one each from Haryana [16], Uttar Pradesh [17], Himachal Pradesh [18] and from Andhra Pradesh [19] two from Gujarat [20,21], and one each from Arunachal Pradesh [22] Andhra Pradesh [23], Tamil Nadu [24] and Kerala [25]. Thus, the total number of authentic cases of blastomycosis reported so far from India is ten.…”
Section: Introductionmentioning
confidence: 99%